Catalytic wet air oxidation of bisphenol A aqueous solution in trickle-bed reactor over single TiO2 polymorphs and their mixtures. Issue 2 (April 2018) - Žerjav, Gregor; Kaplan, Renata; Pintar, Albin
Graphical abstract: Two series of TiO2 polymorphs (anatase (A and A1), rutile (R and R1), brookite (B and B1)) and nanocomposite mixtures of TiO2 polymorphs (anatase A/rutile R (AR), anatase A/TiO2 -B polymorph (ATB), anatase A1/rutile R1/brookite B1 (ARB)) were synthesized and tested in the process of catalytic wet air oxidation (CWAO). The key factor enabling enhanced activity in the CWAO process is high BET specific surface area of the catalysts, which can be compensated either by the presence of appropriate crystallinity, or improved charge separation. Most suitable for long-term use are catalysts A, A1 and ATB. Highlights: Enhanced catalytic activity is obtained with high specific surface area catalyst. The ratio of crystallinity/specific surface area influences catalyst activity in CWAO. Improved charge separation in ARB increases catalyst activity in CWAO process. Strong acidic sites favor accumulation of carbon deposits on the catalyst surface. Catalysts A, A1 and ATB are appropriate for use in long-term CWAO process. Abstract: In this study, two series of TiO2 polymorphs (anatase (A and A1), rutile (R and R1), brookite (B and B1)) and nanocomposite mixtures of TiO2 polymorphs (anatase A/rutile R (AR), anatase A/TiO2 -B polymorph (ATB), anatase A1/rutile R1/brookite B1 (ARB)) were synthesized and tested in the process of catalytic wet air oxidation (CWAO). The goal was total removal of the endocrine-disrupting chemical bisphenol A and its intermediates from a model aqueous solution. TiO2 polymorphs A1, B1 and R1 were prepared with a similar synthesis procedure and from the same TiO2 precursor to investigate the influence of catalyst preparation on their performance. To discover which is the main driving property of the catalyst that enables enhanced BPA degradation and mineralization in the CWAO process, different surface, textural and morphological characterization techniques (XRD, SEM, UV–vis-DRS, FT-IR, TG and N2 sorption) were used. CHNS elemental analysis was applied to reveal which of catalysts is suitable for use in a long-term CWAO process. Characterization and catalytic tests of solids examined show that the key factor enabling enhanced activity in the CWAO process is high BET specific surface area of the catalysts. It was found that low specific surface area of a solid can be compensated either by the presence of an appropriate crystallinity, or improved charge separation. Catalysts A, A1 and ATB showed encouraging results of BPA degradation and mineralization in the CWAO process and would also be appropriate for long-term use, since negligibly small amounts of carbonaceous deposits were accumulated on the surface of these solids during tests performed in the period of 40 h.